2012
DOI: 10.2166/wh.2012.071
|View full text |Cite
|
Sign up to set email alerts
|

A community-based approach to promote household water treatment in Rwanda

Abstract: Treatment of drinking water at the household level is one of the most effective preventive interventions against diarrhea, a leading cause of illness and death among children in developing countries. A pilot project in two districts in Rwanda aimed to increase use of Sûr'Eau, a chlorine solution for drinking water treatment, through a partnership between community-based health insurance schemes and community health workers who promoted and distributed the product.Evaluation of the pilot, drawing on a differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Evaluation of the pilot, drawing on a difference-in-differences design and data from pre- and post-pilot household surveys of 4,780 households, showed that after 18 months of pilot implementation, knowledge and the use of the product increased significantly in the two pilot districts, but remained unchanged in a control district. The pilot was associated with a 40–42 percentage point increase in overall use [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the pilot, drawing on a difference-in-differences design and data from pre- and post-pilot household surveys of 4,780 households, showed that after 18 months of pilot implementation, knowledge and the use of the product increased significantly in the two pilot districts, but remained unchanged in a control district. The pilot was associated with a 40–42 percentage point increase in overall use [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Access to resources such as latrines (8,11,31,46,56,61,62), water (33,50,60,63,64) and handwashing facilities (62) can be driven by diffusion. When these facilities or the idea of them are new (i.e.…”
Section: Accessmentioning
confidence: 99%
“…Women communicate with the committees about system breakdowns and without whom, such information sharing that lead to repair may not occur (50). Such active communication reflects ownership and indicate a willingness to work together and build connections within the community which promotes continuous access by facilitating ongoing response to maintenance issues (32,47,59,63).…”
Section: Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…If the cause of a specific disease is understood or at least well-characterized, then the spread of that disease within a community can be reduced to a minimum or completely eradicated. Supplying human communities with safe drinking water has been established as a necessity, thus warrants monitoring and scrutiny [1][2][3][4], to mitigate against waterborne diseases.…”
Section: Introductionmentioning
confidence: 99%